Islamic Boarding Education Management Reform: Transformation Strategies to Improve Competitiveness and Relevance - Mochamad Arif Faizin (STAI Hubbulwathan Duri, 2024)
This study explores the reform of Islamic boarding school (pesantren) education management and transformation strategies aimed at enhancing competitiveness and relevance in the context of globalization and modern educational challenges. The focus is on understanding how pesantren can adapt and thrive in the evolving educational landscape. Utilizing a qualitative approach, this literature review examines various sources related to pesantren education management reforms and transformation strategies implemented in several Indonesian pesantren. The study systematically analyzes existing literature to identify key themes and insights. The findings reveal significant challenges faced by pesantren, including outdated management practices, limited resources, and resistance to change. However, several pesantren have successfully implemented transformation strategies such as curriculum modernization, the integration of technology in teaching, and the development of partnerships with external educational institutions. These strategies have significantly improved the competitiveness and relevance of these institutions. The study highlights the critical role of stakeholders, including educators, administrators, and policymakers, in driving the reform process. Effective leadership, community involvement, and continuous professional development are identified as crucial factors in achieving successful transformations. The insights gained underscore the importance of adaptive and innovative approaches in education management to meet contemporary demands. This research provides valuable insights into the strategies and challenges of reforming pesantren education management. The successful implementation of transformation strategies can enhance the competitiveness and relevance of pesantren, enabling them to meet the demands of modern education and globalization. Future research should focus on longitudinal studies to assess the long-term impact of these reforms and explore additional strategies to further improve pesantren education management.